SWIFT Detection of SPIO Labeled Stem Cells Grafted in the Myocardium - Zhou, Rong (2010)
We report initial results from studies using SWeep Imaging with Fourier Transformation (SWIFT) to detect superparamagnetic iron oxide (SPIO) particle-labeled stem cells in the rat heart. In experiments performed on phantoms containing titanium balls or SPIO-labeled cells, frequency-shifted signals surrounding the paramagnetic objects produced a pile-up artifact in SWIFT images, while total signal intensity was retained to a much greater extent on SWIFT images as compared to gradient echo images. SWIFT images of excised and in vivo hearts showed (a) reduced blooming artifact as compared with gradient echo images, which helped reduce ambiguity in the detection of SPIO labeled cells, (b) enhancement of off-resonance signals relative to the background in the imaginary component of images, and (c) detailed myocardial anatomy in magnitude images which provided anatomical reference. These features suggest SWIFT can facilitate the detection of SPIO-labeled cells in the cardiovascular system.